The Association between Metaplasia and Gastric Malignancy with Helicobater pylori Infection - Riki Tenggara; Visakha Revana Irawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Background: Helicobacter pylori (H. pylori) infection is the main cause of peptic ulcer disease, gastric mucosa metaplasia, and gastric malignancy. The hypothesis of this study is whether there’s an association between metaplasia and gastric malignancy with H. pylori infection.Method: We conducted a retrospective study on 1.127 dyspepsia subjects who performed endoscopy between 2001 to 2011 at a hospital in North Jakarta. Data is obtained based on endoscopy and histopathology data. Investigation of H. pylori in this study using histopathology examination.Results: Of the 1.127 dyspepsia subjects who performed endoscopy and biopsy, there were 130 (11,54%) H. pylori-positive subjects. Gender proportion was composed of 55,37% men and 44,63% women, with median age was 47 years. On the histopathology examination, we obtained 45 metaplasia subjects with median age of 45 years and 7 malignancy subjects with median age of 64 years. Metaplasia was found in 33 of 997 (3,31%) H. pylori-negative subjects and 12 of 130 (9.23%) H. pylori-positive subjects. All gastric malignancy subjects had H. pylori-negative results.Conclusion: There was an association between metaplasia and H. pylori infection, but no association between gastric malignancy and H. pylori infection.